Effect of In Ovo Ascorbic Acid Injection and Thermal Manipulation During Incubation on Intestine Morphology of Broilers Reared under Cold and Heat Stress - Sgavioli, S. (2022)
It was investigated if pre-incubation ascorbic acid (AA) injection in fertile eggs incubated at high temperature impacts the performance, the yield of carcass and parts, and the intestine morphology of broilers reared under heat stress. Three thousand Cobb (R) fertile broiler eggs were randomly distributed according to weight into three incubations treatments (eggs not injected with AA and incubated at 37.5 degrees C; eggs not injected with AA and incubated at 39 degrees C; and eggs injected with 6 mu g AA/100 mu L water prior to incubation and incubated at 39oC). The hatched birds were reared at thermoneutral, cold, and hot house temperatures. Broilers reared under hot temperature presented lower feed intake and weight gain than the broilers of the different rearing temperatures. Egg incubation at 39.0 oC and 39.0 oC + AA reduced broiler viability. Carcass and cut yields were not influenced by incubation and rearing procedures. Duodenal goblet cell count was lower in broilers from eggs of the treatment 39oC + AA than in broilers from the other incubation treatments and in broiler rearing in hot temperature. In the jejunum, the goblet cell counts were higher in broilers that were reared under hot than thermoneutral temperatures. The incubation treatment of 39 oC+AA increased the goblet cell counts in the ileum of broilers reared under cold temperatures. Rearing temperature influenced the duodenal villi counts, which were lower under cold rearing conditions than in the two other rearing temperatures. The results showed that egg incubation at 39 degrees C, independently of ascorbic acid injection, did not produce an effective epigenetic heat adaptation in broilers.